Canadian Association of Gastroenterology Launches Human Resource Planning Initiatives - Desmond Leddin (Canadian Journal of Gastroenterology)
In 2002, the Canadian Association of Gastroenterology (CAG) conducted a survey of the membership, the results of which were reviewed and developed by the Past Presidents' Council into a long term strategic plan. Survey findings and the resulting strategic plan were published earlier this year in The Canadian Journal of Gastroenterology and can be reviewed on the CAG Web site at http://www.pulsus.com/Gastro/18_01/Pdf/newe_ed.pdf and http://www.pulsus.com/Gastro/18_02/Pdf/newe_ed.pdf. Members repeatedly noted the importance of collecting statistics on gastroenterology in Canada and addressing human resource issues.